A Qualitative Analysis of Remote Employees' Work-Life Harmonization Practices and Their Gendered Discourses : N/A - Simionescu (Vlăsceanu), Maria (Calitatea Vieții, 2024)
This study explores the gender dynamics of work ‒ life harmonization among remote workers in Romania, with a focus on gender as a social structure. The paper’s goal is to discover the personal activities performed by employees during remote workdays and the associated gendered discourses. The study employed a qualitative approach, utilizing semi-structured interviews to explore the subject. Data was collected through video call interviews with 22 parents working full-time remotely or in hybrid arrangements. The sample was selected using quota and snowball sampling techniques. The research identifies a significant time bind conflict for women, who often juggle household chores and childcare, alongside professional duties during remote workdays, experiencing stress and guilt as a result. In contrast, men typically prioritize leisure, and delegate childcare responsibilities, underscoring a disparity in how domestic tasks are shared. The study reveals that the time bind conflict forces women to adjust and develop practices, such as carrying out professional and domestic work activities simultaneously, or doing housework and childcare during work breaks in the remote working days. Our study highlights that such practices can significantly heighten women's stress suggesting that future research should focus specifically on stress levels among remote workers. The paper reveals that, while remote work offers many potential benefits, it can disadvantage women. To ensure that remote work truly supports the harmonization of work ‒ personal life for both men and women, inclusive work structures are needed to address these gender-specific challenges.